Porte cochere at intersection of Mahapalika Marg and DN Road - Ghosh, Ayan (2023)
The main entrance to the BMC building is positioned at the elbow of the V-shaped plot, facing CSMT. The entrance has a six-pillar porte cochère (coach gateway). This was originally designed for horse-driven coaches but was later adapted for motor vehicles.